M-BITION (Microtechnologi Biomethal Remediation): Remediasi Lahan Pasca Tambang Berbasis Mikroorganisme Terinduksi Dalam Sel Tanaman Hiperakumulator Di Provinsi Riau - Syahabudin Ahmad; Fauzan Alamsyah Nasution (Jurnal Kebijakan Pembangunan dan Inovasi, 2019)
Riau is one of the provinces that has a large natural resource potential, one of the natural resources utilized in the mining industry is petroleum. The petroleum mining industry in Indonesia has problems in the post mining period. Problems that occur at the time of post-mining is the presence of petroleum contamination which causes critical land. Petroleum has toxic compounds, namely hydrocarbons and heavy metals. Biological remediation efforts are a solution in remediating petroleum in post-mining land. Innovations that can be made with the use of Microtechnology Biomethal Remediation (M-BITION). MBITION is an attempt to introduce sorghum plant cells by using Pseudomonas putida as bioremediation of post-mining land in Riau Province. The study objective was to assess the use of P. putida induced in sorghum plant tissue (MBITION) in tackling environmental pollution and increasing land productivity. The method was documentary study. The data used in making references and making ideas are obtained from various library sources consisting of books, magazines, electronic media, theses, theses, dissertations and scientific journals. The data that has been collected was analyzed using document content analysis (content analysis document). M-BITION could be used as a remediation of oilcontaminated land that was easy to apply, economical, safe for the environment and fast process. P. Putida will increase the protection and growth of sorghum plants and will enrich biological agents on contaminated land. (This manuscript was a winners of the 23rd National Conference on National Technology Awakening Day (HAKTEKNAS) 2018).